Dietary utilization of mealworm frass in rabbit feeding regimes and its effect on growth, carcass characteristics, and meat quality - Radwan, Mohamed A.; Maggiolino, Aristide; Hassanien, Hanan A. M.; Palo, Pasquale D.; El-Kassas, Nabila E. M.; Abbas, Hassan S.; Salem, Abdelfattah Z. M. (Frontiers in Veterinary Science, 2023)
This study aimed to shed light on the use of mealworm (Tenebrio molitor) frass (TMF) in rabbit diets and its effects on growth performance, blood profiles, rabbit meat quality, and fatty acid profiles. A total of 48 Gabali rabbits were divided equally and randomly into four groups to be fed one of four dietary treatments: a control (T0) group and three TMF groups, which included TMF meal at 1 (T1), 2 (T2), and 3 (T3) %, respectively. The rabbits were fed on isonitrogenous and isoenergetic diets for 11 weeks, and the growth performance data were recorded. Six rabbits per group were slaughtered at the end of the 11th week, then the pharmacochemical parameters and carcass traits were measured, and meat quality and fatty acid profiles were analyzed. The results indicated that the growth performance of different groups was similar (P > 0.05). The levels of globulin, glucose, and alanine transaminase (ALT) were lower in the mealworm frass groups compared with the control group. Carcass traits were not affected by experimental regimes. Fat was higher in the TMF treatment groups, while moisture was lower compared with the control group. The shear force had a lower value in the treatment groups T3 and T2 compared with the control group. The highest values of redness and chroma (color parameter) of rabbit meat were observed in the treatment groups vs. the control group. Moreover, the proportion of total saturated fatty acids in the meat of rabbits that were fed on the T2 and T3 diets was higher compared to those fed on the control (i.e., T0) and T1 diets. Furthermore, the proportion of monounsaturated fatty acid was higher in the T2, T3, and T1 groups vs. T0 rabbits, whereas the PUFA proportions were lower. It could be concluded that frass has great potential to be used as a partial substitute for rabbit diets.